2017
DOI: 10.1002/jmv.24976
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of hepatitis C virus in end‐stage renal disease patients under hemodialysis

Abstract: New direct-acting antiviral (DAA) agents are in development or already approved for the treatment of chronic hepatitis C virus (HCV) infection. The effectiveness of these drugs is related to the previous existence of resistant variants. Certain clinical conditions can allow changes in immunological characteristics of the host and even modify genetic features of viral populations. The aim of this study was to perform HCV molecular characterization from samples of end-stage renal disease patients on hemodialysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…28 Another point of concern is the phenomenon of intermittent viremia, which is not only epidemiological, but also an inconvenience in the control of nosocomial transmission, since the results can be misinterpreted, classifying a patient with active infection as non-virememic. 18,20,29,30 The use of molecular tests with low detection levels should always be recommended.…”
Section: Hcv Tracking In the Dialysis Roommentioning
confidence: 99%
“…28 Another point of concern is the phenomenon of intermittent viremia, which is not only epidemiological, but also an inconvenience in the control of nosocomial transmission, since the results can be misinterpreted, classifying a patient with active infection as non-virememic. 18,20,29,30 The use of molecular tests with low detection levels should always be recommended.…”
Section: Hcv Tracking In the Dialysis Roommentioning
confidence: 99%
“…Cytotoxic T lymphocytes and natural killer cells are necessary for the control of viral infection. A functional exhaustion of antiviral lymphocytes is reported in COVID-19 patients (Zheng et al, 2020a;Alves da Silva et al, 2018). However, there is still limited evidence for the predictive role of lymphocyte count in predicting the severity of COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment-induced viral resistance can be defined as the positive selection of viral variants with reduced susceptibility to DAAs. 40 The presence of naturally occurring RASs to DAAs has been reported in patients from Europe, the US and Japan, while there are few studies demonstrating naturally occurring GT1 mutations in Latin America.…”
Section: Discussionmentioning
confidence: 99%
“… 44 Another paper from our group demonstrated that HCV genome variability and number of mutations were higher in HD patients when compared to non-HD patients. 40 …”
Section: Discussionmentioning
confidence: 99%